Detailed water-use feedback: A review and proposed framework for program implementation. (December 2016) - Liu, Ariane; Giurco, Damien; Mukheibir, Pierre; White, Stuart
Abstract: Smart water metering (SWM) introduces new opportunities to engage householders about water use based on detailed information. Water utilities must decide how to embrace these opportunities, but remain hesitant due to limited available experience and knowledge, which risks delaying the benefits of involving householders more fully in SWM and more sustainable water consumption. An implementation framework is developed outlining the key strategic, practical and evaluative elements in decision-making for detailed feedback programs by drawing on the literature and first-hand experiences of two feedback trials involving SWM. Existing approaches are reviewed and recommendations are provided to advance more well-considered approaches and realise benefits regarding sustainable water use. Highlights: Smart metering presents new opportunities to engage householders about water use. Experiences from two household water-use feedback trials are structured. The literature on smart metering for water and feedback is reviewed. A program implementation framework for detailed water-use feedback is developed. Water utilities can target efforts that contribute to sustainable water usage.